Black is the new orange : flight initiation distance of a tropical forest bird in relation to human clothing colour - Jason J., H. Teo; Michael A., Weston; Caroline, Dingle; Daphawan, Khamcha; Mohd Azlan, Jayasilan; George A., Gale (Informa UK Limited, 2024)
Avitourism has multiple conservation and economic benefits but can pose potential harm to some bird populations. To mitigate the potential impacts of avitourism on birds, researchers can use flight initiation distance (FID) to quantify the tolerance of animals to perceived threats, thereby informing management. This study focused on whether clothing colour used by avitourists (orange, camouflage, and black) affected the FIDs of White-rumped Shama Copsychus malabaricus (n = 123) in a protected area in northeastern Thailand. Camouflage clothing evoked significantly shorter FIDs than orange and black clothing, which elicited statistically similar FIDs. The results of this study aligned with the colour concealment hypothesis, which suggests that clothing colour resembling the forest environment reduces detectability, which results in shorter FIDs. As such, clothing colour may mediate disturbance caused by avitourists. Given that at least one species of Southeast Asian tropical forest bird adjusts its FID in relation to clothing colour, FID studies on additional Asian tropical bird species and clothing colours are encouraged.